PENGUJIAN FAKTOR PENENTU PRILAKU PATUH MEMBAYAR ZAKAT HARTA DARI PERSPEKTIF THEORY OF PLANNED BEHAVIOR - Zaitul Zaitul; Syafri Husen; Mukhlizul Hamdi (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Riau, 2020)
Zakah compliance behaviour among Muzzaki has been discussed by academics and practitioners. However, less attention has been paid about how the compliance behaviour and what factors determine this Zakah compliance in Padang society. Therefore, this study aims to investigate the determinants of Zakah compliance behaviour from perspective of Theory of Planned Behaviour. Ten hypotheses are developed and tested in this study. Nine-four respondents filled and returned the questioner. Simple, multiple and hierarchal regression analysis are applied to gain the result. The result show that three hypotheses are accepted (i) perceived behaviour control has a significant effect on an intention to pay zakah, (ii) subjective norm has a significant relationship with zakah compliance behaviour, and (iii) an intention to pay zakah also has a significant impact on zakah compliance behaviour. Practically, the government can increase Ummah zakah compliance behaviour by improve an muzzaki’s intention to pay zakah through reduce the barriers to pay zakah and improve successful factors. This study theoretically contribute to theory of planned behaviour partially